JD-R Model: Pengaruh Sumber Daya, Keterikatan Kerja, dan Tuntutan terhadap Kinerja Karyawan - Irvan, Muhammad; Zamralita; Markus Idulfilastri, Rita (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
PT X is ceramics manufacturer in Tangerang, with indications of decline in performance over last 3 years. The assumption of decreased performance is due to lack of Job Resources, excessive work demands and existence of counterproductive behavior. In addition, the factors that can affect decreased performance are the lack of work engagement. This tudy aims to measure how the role of job resources affects job performance through work engagement as a mediator and job demands as moderator. Employees with minimum working period of 1 year and minimum staff position at PT X who will participate in research. Performance measurement tools uses IWPQ with 18 items statements, Job Resources and Job Demands uses JD-RQ tool with 17 Job Resource items and 23 Job demands items, Work Engagement uses UWES as measurement tool with 9 items statement. The sampling technique uses convenience sampling. The research sample is 120 with 17 data outliers. We Analyze with model 7 Bootstrapping for moderation and mediation effect were used to test the hypothetical model using SPSS 27. The results stated that Job Resources affect performance mediated by work engagement, but not moderated by job demands. Focusing on practitioner implications, companies need to increase work resources to employees in order to improve their performance, of course, by accommodating higher work attachment. Moreover, companies need to consider increasing compensation and benefits such as benefits, gathering events, training for all employees with staff levels and above so that they are more optimal at work.